1980
DOI: 10.1002/cne.901910403
|View full text |Cite
|
Sign up to set email alerts
|

Ascending projections of the inferior colliculus in the cat: An autoradiographic study

Abstract: The ascending projections of the inferior colliculus (IC) in the cat were traced by the autoradiographic method, with special reference in the differenial projections of each subnucleus of IC. The laminated ventrolateral part of the central nucleus of IC (CNv) projects to the ventral and medial divisions of the ipsilateral medial geniculate body (MGB). The projections to the ventral division are topographically organized in the mediolateral direction, the terminals being arranged in the form of lamina, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
1
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(87 citation statements)
references
References 46 publications
9
76
1
1
Order By: Relevance
“…Supporting this statement, an independent group of animals submitted to the same procedure, except for the pairing of tone with footshock, showed reliable learning rates comparable to those from typical avoidance-escape procedures that utilize an auditory stimulus paired with electric shock as the unconditioned stimulus (21,22). One possible explanation for these surprising results is that repeated electrical stimulation of tomical connections between the inferior colliculus and these structures (17,18). The present results show that rats quickly learn to make a shuttling response in order to avoid or escape from electrical stimulation of the inferior colliculus.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Supporting this statement, an independent group of animals submitted to the same procedure, except for the pairing of tone with footshock, showed reliable learning rates comparable to those from typical avoidance-escape procedures that utilize an auditory stimulus paired with electric shock as the unconditioned stimulus (21,22). One possible explanation for these surprising results is that repeated electrical stimulation of tomical connections between the inferior colliculus and these structures (17,18). The present results show that rats quickly learn to make a shuttling response in order to avoid or escape from electrical stimulation of the inferior colliculus.…”
Section: Discussionmentioning
confidence: 64%
“…It is likely that the inferior colliculus may be responsible for the elaboration of aversion and fear-like responses, together with other structures of the brain aversion system, such as dorsal periaqueductal gray matter and amygdala. As a matter of fact, there are important connections between the inferior colliculus and the dorsal periaqueductal gray matter (17). Furthermore, recent findings from this laboratory have shown that lesion of the central nucleus of the amygdala attenuates, while lesion of the basolateral complex enhances the aversive consequences of the electrical stimulation of the inferior colliculus (18).…”
Section: Discussionmentioning
confidence: 92%
“…DCIC and LN do project to the MGB, like the ICC does, but they mainly synapse on cells in the medial and dorsal regions (Calford and Aitkin 1983), along a purported modulatory pathway of the auditory system (Lee and Sherman 2010). These regions also send output to the SC (Kudo and Niimi 1980).…”
Section: Subdivisions Of the Ic And The Representation Of Sound Frequmentioning
confidence: 98%
“…Indeed, the PO receives auditory inputs from the external, pericentral, and brachial nuclei of the inferior colliculus (Kudo and Niimi, 1980;Kudo et al, 1984;Linke et al, 2000) as well as the dorsal nucleus of the lateral lemniscus (Kudo et al, 1983). In addition, PO receives visual and somatosensory inputs from the superior colliculus and spinal cord (for review, see Jones, 1985).…”
Section: Introductionmentioning
confidence: 99%